PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEBSITE PADA MATA PELAJARAN PAI DAN BUDI PEKERTI KELAS X DI SMK NEGERI 1 TEGALSARI - Riza Faishol; Al Muftiyah; Alvin Dwiki Bastiar (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
The purpose of this study is to explain the development and feasibility of website-based learning media in The Subject of Pai And Ethics Class X at SMK Negeri 1 Tegalsari. This research uses the research and development (R&D) method using the Brog And Gall development model which has 10 development steps but the researcher only limits the available steps to 9 steps, namely: 1) Potential and Problems, 2) Needs Analysis, 3) Product Design, 4) Design Validation, 5) Product Revision, 6) Product Trials, 7) Product Revision. The research data were obtained by non-test techniques. The non-test instruments used are interviews, observations, questionnaires for subject teachers and students, validity test questionnaires for media experts and material experts as well as documentation in the form of photos and curriculum documents. The results of this study show that website-based learning media products are suitable for use in class X of SMK Negeri 1 Tegalsari which refers to the results of feasibility tests according to experts, namely media experts by 88%, material experts by 83% and users (Teachers) by 81%. It is also stated that it is feasible to get from the results of individual / student trials, namely 84%, small group trials, namely 83.5% and field trials of 84%, so it can be interpreted that website-based learning media is suitable for use in learning PAI and Ethics chapters enjoying seeking knowledge and the beauty of sharing class X knowledge at SMK Negeri 1 Tegalsari in 2021/2022.